The Effect of Transformational Leadership and Organizational Culture on Work Commitments in SMP Jakarta Selatan - Robertus; Matin; Heru Santosa (Technium Social Sciences Journal, 2020)
The purpose of this study is to determine the effect of transformational leadership, organizational culture on work commitments in junior high schools throughout South Jakarta. The study was conducted on work commitments to the study population 84 and sample selection 69 employees of the Education Office of North Bengkulu. This research uses a quantitative approach with a path analysis method. The results showed that: (1) transformational leadership had a direct positive effect on work commitment, (2) organizational culture had a direct positive effect on work commitment, (3) transformational leadership had a direct positive effect on organizational culture. Based on the results of research to improve teacher work commitments that need to be improved is Transformational leadership, organizational culture.